Clinicians’ perceptions of Norwegian women’s experiences of infertility diseases - Fernandes, A.; Skotnes, L.- L.; Major, M.; Falcão, P. F. (International Journal of Environmental Research and Public Health, 2020)
Background: Norway has one of the best health systems in the world. However, it has a low birth rate, which decreased by 21.2% between 2009 and 2018, and one of the highest rates of infertility prevalence. The aim of this study is to understand how Norwegian doctors perceive female infertility diseases, namely those that are more difficult to diagnose and to treat, and that are more common in their practice. Method: Descriptive qualitative study was conducted with gynecologists and general practitioners. The sample resulted from the establishment of five criteria and on the doctors’ acceptance to participate in this study. Our sample comprised thirteen highly qualified and experienced doctors. Qualitative content analysis was the method chosen to analyze the collected data. Results: Clinical diseases (polycystic ovary syndrome, endometriosis and vulvodynia) and consequences of these diseases were the pinpointed themes. These led to a set of sub-themes: the main symptoms and the treatment of the diseases, from the perspective of both women and doctors (stigmatization, disturbances in women’s daily life, diagnostic delay, and governmental support). Conclusions: The three most relevant disorders mentioned were polycystic ovary syndrome, endometriosis and vulvodynia. These diseases cause several impacts on the lives of women, because they feel stigmatized and limited in their daily life and sexuality, and the diagnosis of these diseases takes too much time. Governments should better redistribute the financing of women’s health and allocate resources to specialized centers.